Avaliação do remodelamento cardíaco e estresse oxidativo em ratas infartadas submetidas a terapia de fotobiomodulação e carvedilol - Grandinétti, Vanessa dos Santos (2018)
Heart failure (HF) has as its main etiology myocardial infarction (MI), followed by cardiac remodeling, associated with the effective participation of oxidative stress in its genesis. Our objective was to analyze the effects of Carvedilol therapy and photobiomodulation with low lavel laser therapy (LLLT) on cardiac remodeling and oxidative stress in rats infarcted with HF. The study was approved by the Committee on ethics in the use of animals of the University Nove de Julho under number 0016/2016. The final sample size was 127 rats, arranged in 5 experimental groups: SHAM, IM, IMC (Carvedilol treated myocardial infarction), IML (LLLT treated myocardial infarction), IMCL (Carvedilol treated myocardial infarction associated with LLLT ). The results show increase of body weight over the study period in the SHAM, IMC and IML groups, respectively. The aerobic physical performance of all infarcted groups, regardless of any intervention, presented depression at 29 days of study. LV morphological assessments demonstrate that therapies alone or in combination did not result in benefits, and LV systolic and diastolic function data demonstrate that all infarcted animals exhibited performance depression on systolic function 3 days after coronary occlusion, however, significant improvement was observed in the IMCL group at the end of the study. Oxidative stress decreased in the IML group compared to the IM group. Benefits in the expression of carbonylated proteins were evident only in the IMCL group, compared to the IM group. Data on the activity of antioxidant enzymes superoxide dismutase (SOD) and catalase (CAT) in myocardium remote from infarction, showed that there was no benefit of the isolated or combined therapies in SOD and CAT activity in the IMCL group, was significantly higher than values found in the other experimental groups. Survival curves did not show significant differences between groups over 30 days of follow-up. We conclude in this study that Carvedilol and photobiomodulation therapy with LLLT have similar effects on post-infarction HF, considering changes in physical performance, cardiopulmonary biometry and left ventricular morpho-functionality. However, a local anti-inflammatory effect was more evident in animals treated with LBI. In addition, the combination of therapies resulted in attenuation of myocardial hypertrophy and improvement of LV FEAT.